The Application of Behavioral Aspects to the Accounting System Pt Perkebunan Nusantara Vi (Ptpn Vi) Jambi Region - Ratih Kusumastuti; Iskandar Sam; Misni Erwati; Mifthahul Nurzanah (Indonesian Journal of Business Analytics, 2024)
The purpose of this study was to present empirical support for the use of behavioral features in the accounting system. We carried out our investigation at PT Perkebunan Nusantara VI (PTPN VI). The sample technique used was called purposeful sampling. The research sample consisted of 45 respondents. two types of statistical analysis: descriptive and inferential. It is anticipated that the literature on accounting information systems and behavioral accounting will benefit from the study's examination of the behavioral components of the accounting system. Because understanding the behavioral characteristics of the accounting system can be taken into account when making decisions or policies for the company's advancement, the practical benefits of the research's findings assist the business. The results demonstrated that the accounting system is impacted by motivation. At PT. Perkebunan Nusantara VI (PTPN VI) Jambi Region, perception has no discernible impact on the accounting system, learning has no effect, and emotion has a partial impact.